86.7k views
1 vote
The answers to 13 and 20 and how there done.

The answers to 13 and 20 and how there done.-example-1
User Iacchus
by
5.7k points

1 Answer

3 votes

The sum and product of two functions
f(x) and
g(x), i.e.
(f+g)(x) and
(f\cdot g)(x) respectively, are simply defined as the sum and product of the expressions that define each function.

So, as for exercise 13, we have


(f\cdot g)(x) = f(x)\cdot g(x) = (2x^3-5x^2)(2x-1) = 4 x^4- 12 x^3 +5 x^2

Similarly, as for exercise 20, we have


(g + f)(t) = g(t) + f(f) = (2t+5) + (-t^2+5) = -t^2 + 2t + 10

User Jojo Tutor
by
6.5k points